Optimal relay assignment for fairness in wireless cooperative networks. (23rd February 2012) - Xu, Hongli; Huang, Liusheng; Liu, Gang; Zhang, Yindong; Huang, He
Under this cooperative communication, the selection of relay node significantly affects the performance of wireless networks. The previous researches optimised the Max–Min Fairness (MF), which may drastically decrease the network throughput. Thus, this paper studies the fairness–aware relay assignment to improve the network throughput. First, we develop the PFRA algorithm, which assigns the relays by saturated bipartite matching, to reach the proportional fairness. Next, a distributed version of Proportional Fairness Relay Assignment (PFRA) algorithm is also proposed. Moreover, lexicographical Max–Min fairness is achieved by Lexicographical Fairness Relay Assignment (LFRA) algorithm. We formally prove the optimality of above three algorithms. The experimental results show the efficiency of the proposed algorithms.